Course of ankle-brachial-index 12 months after intravascular lithotripsy in calcified peripheral lesions. (3rd October 2022) - Aftanski, P; Thieme, M; Schulze, P C; Klein, F; Moebius-Winkler, S; Kretzschmar, D
Abstract: Background: Intravascular lithotripsy (IVL) is a relatively novel treatment option for calcified lesions in peripheral artery disease. Little is known about the mid to long-term functional status of the patients and target lesion revascularization rate (TLR) after IVL only procedure. Purpose: To evaluate the course of ankle-brachial-index (ABI) and to assess the rate of revascularization 1 year after intravascular lithotripsy performed on calcified peripheral lesions. Methods: Between December 2018 and January 2021 IVL was performed on 61 limbs of 51 patients presenting with Rutherford classes 2–5. Ankle-brachial-index (ABI) was documented before the procedure as well as 1 day, 6 months and 1 year after the procedure within a single center real-life registry. Further endpoint was revascularization with PTA or peripheral bypass surgery. The vast majority of cases were done as IVL only procedure (58%) All procedures were done in upper leg/pelvic stenosis. Results: ABI measurement after 12 months was done in 42 of 51 patients (82%). Three pts were missed due to media sclerosis. Due to loss of follow-up, ABI after 6 months could not be performed on 4/61 patients (7, 8%) and 12-month-ABI in another 8/51 cases (15, 6%). Initial baseline ABI of 0.6±0.26 before the procedure increased to 0.8±0.25 (p<0.0001) one day afterward. After 6 months, the ABI of 0.8±0.27 (n=49; p<0.0001) was still significantly improved compared to baseline. After 1 year, ABI with 0.7±0.22 was still improved, however not significantly different from baseline (Figure 1). Target lesion revascularization was needed in 7 patients (13%), 4 with subsequent IVL, 3 with PTA and 2 with peripheral bypass surgery. Conclusions: In our large single center registry, IVL performed mainly as a stand-alone procedure was safe and effective even after a mid-term follow up. TLR was necessary in 13%, which is lower than in previous published IVL data (20, 7% as in DISRUPT-PAD-II) [1]. ABI after 12 months improved but did maintain statistical significance, compared with other procedure like scoring balloon [2]. Funding Acknowledgement: Type of funding sources: None.